Peranan Pengetahuan Pajak dan Kesadaran Pajak bagi Kepatuhan Pajak Pelaku Usaha E-Commerce - Olivia Afrinadea Chanita; Norman Duma Sitinjak (University of Merdeka Malang, 2021)
Research to examine the role of tax knowledge and tax awareness for tax compliance by e-commerce entrepreneurs. The sample is 50 e-commerce entrepreneurs, obtained by a simple random sample technique. Multiple linear regression was used to analyze the effect of tax knowledge and awareness on tax compliance. The important point of the research results is that knowledge and awareness of taxes owned by e-commerce entrepreneurs have a positive effect on tax compliance.